Wirtschaftliche Konvergenz auf verschiedenen räumlichen Ebenen: Der Konflikt zwischen Kohäsion und Wachstum - Kramar, Hans (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
The analysis of economic disparities within the European Union strongly depends on the regional level considered. Whereas the economic gap between the member states has decreased over the last decades, regional disparities have rather deepened. The reason for these contradictory findings can be found in the increasing disparities within many of the member states: Especially in growing economies the gap between urban centres and rural peripheries tends to widen. The spatial concentration of research and development, high skilled labour, infrastructure and foreign investment in the capitals will therefore suppose-ably become a big challenge for the accession countries, which will have to face increasing international competition. Joining a common market of more than 450 million people means new opportunities, challenges and threats for economic development, which have to be faced by local, regional and national governments as well as by European institutions.EU-policies act in the dichotomy between the conflicting goals of economic growth and cohesion. Since they strongly influence regional conditions for production it is of great political interest whether a certain measure fosters economic efficiency by favouring the highly developed centres or rather enhances convergence by promoting lagging regions. The answer is, however, not trivial and needs closer examination: Measures encouraging regional cohesion on the European level can also increase disparities within a state or a region at the same time. This is the reason why the regional effects of EU-policies have to be analysed on different spatial levels.Dealing with the spatial impacts of various European Policies (Regional Policy, Trans-European Networks, Common Agricultural Policy, Research and Technological Development Policy) there is some evidence that these policies try to compensate the effects of growing competition in the common market by concentrating their efforts on urban growth poles within the underdeveloped countries. Doing that, the European Union comes up to the two conflicting goals of growth and cohesion by promoting efficient economic development in the member states on the one hand and regional convergence on the European level on the other. This approach is of course mainly directed at European objectives and brings about new problems for the member states: According to the principle of subsidiarity the growing divergence within the member states is, however, not a policy task of the European Union but of the member states: Therefore national politics are still required to take on responsibility for these intranational problems by adopting their transport, regional and economic policies to the new challenge.